2022
DOI: 10.3389/fmed.2022.1038315
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, predictors, and outcomes of early hospital readmissions after kidney transplantation: Systemic review and meta-analysis

Abstract: BackgroundEarly hospital readmission (EHR) within 30 days after kidney transplantation is a significant quality indicator of transplant centers and patient care. This meta-analysis aims to evaluate the incidence, predictors, and outcomes of EHR after kidney transplantation.MethodsWe comprehensively searched the databases, including PubMed, Cochrane CENTRAL, and Embase, from inception until December 2021 to identify studies that assessed incidence, risk factors, and outcome of EHR. The outcomes included death-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The authors found no differences in patient survival or graft survival between patients with different BMIs [41]. More recently, a meta-analysis of 17 prospective and retrospective observational articles found no relationship between recipient BMI and the incidence of early hospital readmission within 30 days after KT [42].…”
Section: Outcomes and Complications Of Transplant Surgery Impact Of O...mentioning
confidence: 93%
See 2 more Smart Citations
“…The authors found no differences in patient survival or graft survival between patients with different BMIs [41]. More recently, a meta-analysis of 17 prospective and retrospective observational articles found no relationship between recipient BMI and the incidence of early hospital readmission within 30 days after KT [42].…”
Section: Outcomes and Complications Of Transplant Surgery Impact Of O...mentioning
confidence: 93%
“…Obesity is rising among the adult population, even in patients with kidney failure who need transplants. Obesity is also linked to inferior transplant outcomes and is a relative contraindication to organ transplantation [42]. KT is a life-improvement treatment that results in lower hospitalization rates and significant long-term cost savings to health systems compared to dialysis.…”
Section: Cost-effectiveness Of Bariatric Surgery In Kidney Transplant...mentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, allograft survival was significantly impacted in patients experiencing UTIs (92.1% vs. 96.7%, P = 0.02). Other studies have demonstrated an up to two-fold increase in the risk of graft failure and a substantial increase of patient mortality, following readmission [ 17 ]. Infectious complications, especially UTIs are one of the most important causes for hospital readmission after transplantation.…”
Section: Prevalence and Impact Of Urinary Tract Infections On Healthc...mentioning
confidence: 99%
“…The relatively high incidence of post-transplant EHR is concerning since EHRs have been associated with a severe reduction in health status and substantial healthcare costs. Several kidney transplant studies observed an increased risk of graft failure, patient mortality, and suboptimal graft function with EHR[ 6 - 10 ]. EHRs were also associated with more late hospital readmissions (LHRs), defined as subsequent readmissions within the 1 st year of transplantation after the EHR time frame.…”
Section: Introductionmentioning
confidence: 99%